The Role and Reason Why Armenians Were Selected as Iranian Businessmen During the Shah Abbas’s Era (International Journal of Scientific Research and Management (IJSRM), 2019)
The main purpose of this paper is to examine the function of the Armenians merchant during the Safavid period. Shah Abbas turned to Armenian merchants to implement a silk monopoly policy. This approach also turned to Armenian personal and social experiences and characteristics. The abundance of silk production and its importance as export and strategic commodity, it has led to the adoption of its monopoly policy by Shah Abbas I. (1588-1629). (Falsafi, 77) Followed by the use of qualified Armenian merchants were implement this policy. Hence, it is a question of how the Armenian merchants played a role in the economy and politics of the Safavid. For a closer look at this role, after looking at the little silk collection bag, it has been tried to explain the reasons for the silk monopoly policy as well as the reasons for the use of Armenian businessmen as executors of this policy. Armenian merchants with their individual and group capabilities have been able to find new markets for Iranian silk in global markets. Accordingly, the study of the Armenian merchants shows that they not only affected Iran’s foreign relations and foreign policy but also expanded foreign trade, increased imports of money and goods, the establishment of a balance in foreign trade and the economic situation the social business of the merchants also promoted silk work.